Seismic Loading and Reinforcement Effects on the Dynamic Behavior of Soil Slopes - Vishal S. Ghutke; Anirban Mandal; Anjan Patel (Communications)
Despite the significant research on the seismic stability of earth structures, critical gaps remain in understanding the dynamic response of soil slopes with varying reinforcements. These gaps were addressed in this study by using a small shake table to investigate the dynamic behavior of soil slopes under different conditions. The research examines responses at various frequencies, the effect of reinforcement methods, and the impact of slope height. Results indicate that the higher frequencies and amplitudes lead to increased displacements, while reinforcement reduces crest displacement by 21 to 45%. Steeper slopes (35° and 40°) also show increased displacements by 9 to 65%, compared to a 30° slope. The importance of reinforcement in improving the seismic resilience of soil slopes is highlighted in this study, offering practical insights for engineering design.